Accurate Estimations of Sea‐Ice Thickness and Elastic Properties From Seismic Noise Recorded With a Minimal Number of Geophones: From Thin Landfast Ice to Thick Pack Ice. Issue 11 (21st November 2020) - Moreau, Ludovic; Weiss, Jérôme; Marsan, David
Abstract: Despite their high potential for accurate sea ice properties estimation, seismic methods are still limited by the difficulty of access and the challenging logistics of polar environments. Conventional seismic methods generally require tens of geophones together with active seismic sources for monitoring applications. While this is not an issue for mainland environment, it is restrictive for sea ice and prevents long‐term monitoring. We introduce a method to estimate sea ice thickness and elastic properties from passive recordings of the ambient seismic field with a minimal number of geophones. In comparison with our previous work (Moreau et al.,  2020; https://doi.org/10.1029/2019JC015709 ) where about 50 sensors were used, the number of geophones is reduced by 1 order of magnitude, thanks to a new strategy of inversion of the passive seismic data. The method combines noise interferometry for estimating the elastic properties, with a Bayesian inversion of the dispersion in the waveforms of icequakes for inferring ice thickness, based on passive recordings from only 3–5 geophones, depending on the signal to noise ratio. We demonstrate its potential both on data recorded on thin landfast ice in Svalbard, and on data recorded on thick pack ice in the Arctic ocean. Plain Language Summary: Seismic methods have high potential for monitoring important properties of sea ice, such as its thickness of rigidity. Such data are essential for improving climate models. However, the use of seismic methods is limited by the difficulty of access and the challenging logistics of polar environments. It is therefore essential to reduce as much as possible the instruments required for their application. Conventional seismic methods generally require tens of geophones together with active seismic sources for monitoring applications. We introduce a method to estimate sea ice properties based on the recordings of seismic noise with only three seismic stations, and demonstrate its potential on data recorded in a frozen fjord in Svalbard, as well as on data collected on drifting sea ice in the Arctic Ocean. The method is shown to have very promising potential for long‐term and accurate monitoring of the properties of sea ice. Key Points: The Young's modulus and Poisson's ratio of sea ice are estimated from seismic noise interferometry Bayesian inference is applied to icequake recordings for a simultaneous inversion of the icequake position and sea ice thickness In comparison with our previous work, where about 50 sensors were required, the number of stations is reduced by 1 order of magnitude